(untitled) (The Research of Medical Science Review, 2025)
Academic writing is formal writing used by students in an academic setting. This study explored the challenges encountered by postgraduate nursing scholars in academic writing at the college of nursing AFPGMI Rawalpindi. This study utilized the qualitative approach using exploratory design. The study participants included 25 students of MSCN first semester enrolled for the academic year 2025 and were selected through a purposive sampling technique after obtaining their consent. Data was gathered through a semi-structured focus group interview guide, conducted over three weeks. The interviews were transcribed, and a manual qualitative thematic analysis was performed, resulting in the generation of codes, subthemes, and themes. Results revealed five themes: Pre-existing Knowledge and Expectations, Key Challenges Faced in Academic Writing, Difficulty in organizing information, Coping Strategies and Support Systems, and Suggestions for Programmatic Improvement. This study concluded that Postgraduate nursing students encounter multifaceted challenges in academic writing, shaped by insufficient prior exposure, high expectations, and emotional stress. Yet, their proactive strategies and clear suggestions show a strong desire to succeed. Tailored interventions grounded in Constructivist Learning Theory emphasizing support, collaboration, and guided practice can significantly improve outcomes. Future researchers are encouraged to conduct studies about academic reading and put more stress on writing strategies that must be effective for students.